Zorganizowany rynek kapitałowy elementem systemu finansowego - Banaszczak-Soroka, Urszula (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
Integration of stock markets in EU affects each market in each country. In Poland in 2005 three new acts regulating organisation of stock market were enacted. This new law was based on EU directives. One of the most important changes is abolishing compulsion on regulated market, which means obligation of closing the deal on certain stock market. In new reality there are three independent forms: circulation-regulated market (stock and non-stock), alternative system of circulation and direct transactions. The article shows changes in location of particular parts of stock market in financial system. There are also shown cosequences and influence of this situation on behavior of emitents and investors on this market.
Keywords: rynek kapitałowy; Giełda Papierów Wartościowych; oferta publiczna; rynek finansowy